Estimation of Damping in Layered Welded Structures with Unequal Thickness - Bhagat Singh; Bijoy Kumar Nanda (Shock and Vibration, 2012)
The present work is focused on the study of damping mechanism in layered and welded cantilever beams with unequal thickness. It is observed that a number of vital parameters such as: thickness ratio, pressure distribution characteristics, relative slip and kinematic co-efficient of friction at the interfaces, initial amplitude of excitation, length and thickness of the beam specimen govern the damping capacity of these structures. Experiments have been conducted in order to study the effect of these parameters and validate the developed damping model. The damping model of the structure is found to be in fairly good agreement with the measured data. Finally, the results for the damping capacity are discussed and rationalized.